Working overtime: Quantifying the added workloads of extra periods in starting players during basketball game-play - Fox, J. L.; Stanton, R.; Sargent, C.; O`Grady, C.; Scanlan, A. T. (Journal of Australian Strength and Conditioning, 2018)
Overtime games significantly increase the internal and external workloads imposed on starting semi-professional basketball players compared to regular games, which should be considered by basketball coaches and conditioning staff when implementing recovery and training plans.